Is a Pathological Complete Response Following Neoadjuvant Chemoradiation Associated With Prolonged Survival in Patients With Pancreatic Cancer?. Issue 1 (July 2018) - He, Jin; Blair, Alex B.; Groot, Vincent P.; Javed, Ammar A.; Burkhart, Richard A.; Gemenetzis, Georgios; Hruban, Ralph H.; Waters, Kevin M.; Poling, Justin; Zheng, Lei; Laheru, Daniel; Herman, Joseph M.; et al.
Abstract : Objectives: To describe the survival outcome of patients with borderline resectable or locally advanced pancreatic ductal adenocarcinoma (BR/LA-PDAC) who have a pathologic complete response (pCR) following neoadjuvant chemoradiation. Background: Patients with BR/LA-PDAC are often treated with neoadjuvant chemoradiation in an attempt to downstage the tumor. Uncommonly, a pCR may result. Methods: A retrospective review of a prospectively maintained database was performed at a single institution. pCR was defined as no viable tumor identified in the pancreas or lymph nodes by pathology. A near complete response (nCR) was defined as a primary tumor less than 1 cm, without nodal metastasis. Overall survival (OS) and disease-free survival (DFS) were reported. Results: One hundred eighty-six patients with BR/LA-PDAC underwent neoadjuvant chemoradiation and subsequent pancreatectomy. Nineteen patients (10%) had a pCR, 29 (16%) had an nCR, and the remaining 138 (74%) had a limited response. Median DFS was 26 months in patients with pCR, which was superior to nCR (12 months, P = 0.019) and limited response (12 months, P < 0.001). The median OS of nCR (27 months, P = 0.003) or limited response (26 months, P = 0.001) was less than that of pCR (more than 60 months). In multivariable analyses pCR was an independent prognostic factor for DFS (HR = 0.45; 0.22–0.93, P = 0.030) and OS (HR=0.41; 0.17–0.97, P = 0.044). Neoadjuvant FOLFIRINOX (HR=0.47; 0.26–0.87, P = 0.015) and negative lymph node status (HR=0.57; 0.36–0.90, P = 0.018) were also associated with improved survival. Conclusions: Patients with BR/LA-PDAC who had a pCR after neoadjuvant chemoradiation had a significantly prolonged survival compared with those who had nCR or a limited response.